We Face Forward: Art From West Africa Today. - Balshaw, Maria; Bond, Bryony; Griffiths, Mary; Howes, Natasha; Rice, Alan; Eyene, Christine; Kouoh, Koyo; Himid, Lubaina (Manchester : Manchester Art Gallery, 2012)
Adéagbo, georges ; Amouzou, Hélène ; Anatsui, El ; Azubuike, lucy ; Camara, Mohamed ; Eyongakpa, Em'kal ; Fofana, Aboubakar ; Gaba, Meschac ; Gbré, François-Xavier ; Hazoumè, Romuald ; Armin Kane, Abdoulaye ; Konaté, Abdoulaye ; Maiga, Hamidou ; Malé, Soungalo ; Obodai, Nii ; Ogboh, Emeka ; Oghobase, Abraham ; Okafor, Amarachi ; Okereke, Charles ; Okore, Nnenna ; Olowu, duro ; Osodi, George ; Ouedraogo, Nyaba Léon ; Piniang ; Quarmyne, Nyani ; Raw Material Company ; Sakaly, Abderramane ; Sanogo, Amadou ; Sidibé, Malick ; Tayou, Pascale Marthine ; Toguo, Barthélémy ; Udondian, Victoria ; Zounyekpe, Séraphin
We Face Forward: Art From West Africa Today, Manchester Art Gallery, Manchester, 2 juni tot 16 september 2012
boek